Peningkatan Pengetahuan Efek Samping Obat Antidiabetes melalui Edukasi pada Pasien Diabetes Mellitus di Kelurahan Angke, Jakarta Barat - Meiyanti Meiyanti; Yohana Yohana; Eveline Margo; Sisca Sisca (Jurnal Pengabdian Nasional (JPN) Indonesia, 2026)
Lifestyle changes have contributed to the rising incidence of type 2 diabetes mellitus (T2DM) in major cities, including Jakarta. This condition requires thorough management, one aspect of which is long-term medication adherence. A primary factor that frequently triggers non-adherence is patients' limited understanding of antidiabetic drug side effects. This community service activity aimed to improve long-term medication adherence by strengthening patients' knowledge and understanding of antidiabetic drug side effects through education and direct consultation. The activity was carried out on March 6, 2026, in West Jakarta, using interactive counseling sessions and individual consultations. A total of 30 T2DM patients participated. Evaluation was performed through random blood glucose (RBG) measurement, pre-test and post-test assessments of knowledge on medication side effects consisting of 10 multiple-choice questions, and participatory observation. The results showed a statistically significant increase in the mean knowledge score from 62.3 to 84.7 (p<0.001). RBG testing revealed that 60% of participants had normal levels (<200 mg/dL), while the remaining 40% still exhibited hyperglycemia. During consultation sessions, chronic pain complaints were identified in several participants, potentially prompting unsupervised use of additional medications. The activity proceeded in an orderly manner with active participation from all attendees. The conclusion of this activity is that education and consultation proved effective in raising patient knowledge significantly as an initial step toward improving medication adherence; however, follow-up interventions addressing non-pharmacological management and pain management remain necessary.